Fusobacterium and Colorectal Cancer - Zhou, Ziwei; Chen, Jiewen; Yao, Herui; Hu, Hai (Frontiers in Oncology, 2018)
Colorectal cancer (CRC) is the third most common cancer worldwide and its pathogenesis has been extensively explored over the past decades. Recently, microorganisms in the gastrointestinal tract have emerged as potential etiological agents. In particular, a direct proportional association between Fusobacterium and CRC has been described. Since then, the functional impact of Fusobacterium in CRC development has been studied using various mouse models. Although some epidemiologic studies did not establish an obvious relationship between Fusobacterium and CRC, numerous pathogenic mechanisms leading to the disease have been described. For instance, Fusobacterium can activate the E-cadherin/β-catenin signaling pathway and is associated with particular epigenetic phenotype, such as microsatellite instability (MSI) and hypermethylation, via its strong adhesive and invasive abilities resulting in malignant transformation of epithelial cells. Also, Fusobacterium could alter the tumor microenvironment (TME) significantly by myeloid-derived suppressor cells (MDSCs), tumor associated macrophages (TAMs), and tumor associated neutrophils (TANs) recruitment and local immune suppression. Herein, we provide an in-depth review of the relationship between Fusobacterium and colorectal cancer. In light of the emergence of microbiome-based therapeutics, potential therapies and preventive strategies for colorectal cancer related to Fusobacterium are also discussed.